Traumatic Closed Proximal Muscle Rupture of the Biceps Brachii in Military Paratrooper. (29th August 2019) - Kalinterakis, Georgios; Antonogiannakis, Emmanouil; Rampakakis, Ioannis; Tsialogiannis, Evangelos; Syllaios, Athanasios; Ziogas, Miltiadis
Abstract : Traumatic closed proximal muscle rupture of the biceps brachii has been infrequently cited in the medical bibliography. Early reports of this injury derived from US military during parachute jumps, and it may compromise >4% of injuries at altitude. The mechanism is a direct blow to the upper extremity by static lines. We report a case of traumatic closed proximal rupture of the biceps brachii in a healthy 25 years of age military paratrooper. He was managed with primary surgical repair, and after three years of follow-up, the patient has excellent functional results.